Greed in the history of political economy : the role of self-interest in shaping modern economics - Verburg, Rudi (London ; New York : Routledge Taylor and Francis Group, 2018)
"Since 2008, profound questions have been asked about the driving forces and self-regulating potential of the economic system, political control and morality. With opinion turning against markets and self-interest, economists found themselves on the wrong side of the argument. This book explores how the economics of the past can contribute to todays debates.The book considers how political economy developed, as philosophers probed into the viability of commercial society and its potential to generate positive-sum outcomes. It explores how dreams of affluence, morality and happiness were built upon human greed and vanity. It presents a framework within which to contextualise present-day concerns about limits to growth, and through which we can rethink the basis of our economic system."--Provided by publisher.
chapter 1 Shifting narratives and the emergence of political economy / Rudi Verburg -- chapter 2 The rise of greed in early economic thought -- From deadly sin to social benefit 1 / Rudi Verburg -- chapter 3 The Mandevillean triangle / Rudi Verburg -- chapter 4 Adam Smith$1 (Bs struggle with Rousseau$1 (Bs critique of commercial society /s Rudi Verburg -- chapter 5 Self-interest after Smith -- From passion to behavioural assumption / Rudi Verburg -- r Rudi Verburg.
Keywords: Avarice -- Economic aspects; Economics -- Philosophy